Values and development in Southern Africa - Müller, Hans-Peter, 1954-; Mekgwe, Pinkie; Mhloyi, Marvellous Mynard (Codesria book series., 2013)
Development has been on Africa's agenda for a long time but progress has been both varied and limited, partly due to the diverse levels of the discussions on the challenges and the interventions for tackling them. Africa's greatest challenge is the uneven development within and between its countries, and the pressing issues of extreme poverty in southern Africa, and the continent as a whole. Poverty causes its victims to suffer social exclusion and political repression. In addition, societies that experience poverty are also mostly under continuous threat of ecological disasters and diseases. This book focuses on the social and cultural dimensions of development dynamics and, in particular, the role of values in shaping development. Values are at the core of the hopes and aspirations of individuals, communities, and societies. The book therefore explains the values that motivate and inform African communities and societies, with a view to facilitating a dialogue about sustainable development in Africa among academics, intellectuals, policy and decisionmakers, and the communities themselves.